Humic Acid as Detoxification Substance for Heavy Metal Removal in Laterite Barren Soil - Bin Mat Rahimi, Muhammad Ukasyah Irfan; Embong, Zaidi (Enhanced Knowledge in Sciences and Technology, 2022)
Humic acids and their functional acidic groups are the key factors responsible for metal cation binding for their state and concentration in soils. The objectives of this study are to measure the elemental polluted soil from Pagoh Education Hub, Johor using SEM-EDX and polluted soil functional group using Laser Raman, to characterise the organic compound bonding and functional group for humic acid liquid using Laser Raman and FTIR and to compare the heavy metal concentration between pre and post humic acids chemical treatment. Humic acid is applied to the polluted soil for 3 days within 14 days. The suface morphology of the soil samples weight percentage of main in element in the soil samples like oxygen, silicon, iron and aluminum were obtained through Scanning Electron Microscopy with Energy Dispersive X-Ray (SEM-EDX). Next, Fourier Transform Infra-Red (FTIR) was used identify the functional group of humic acid. Laser Raman was also used to obtain the functional group of humic acid and the soil samples. On the whole, based on the data obtained, humic acid is one of the effective ways to remediate the heavy metal polluted soil.